THE CONTENT AND FEATURES OF THE DISTRIBUTION OF HEAVY METALS (CU, ZN, CD, PB) IN THE "SOIL -NEEDLES AND LEAVES OF TREES" IN DIFFERENT PARTS OF THE CITY OF UST-KAMENOGORSK - V. F. Zaitsev; G. K. Galyamova (Юг России: экология, развитие)
The problems of accumulation of copper, cadmium, lead and zinc in such objects of the environment, soil, pine and spruce needles, leaves, poplar, birch, elm and elm foliose squat on different parts of the city of Ust-Kamenogorsk, Kazakhstan. Shown that the maximum accumulation of TM characterized soil, pine needles (leaves) of the northern, central (residential) areas of the city.